O processo de subjetificação das personagens femininas em Disgrace (1999), de J. M. Coetzee - Oliveira, Angela Aparecida Gonçalves (2008)
The subjectification process of the female characters Soraya, Melanie and Lucy, in J. M. Coetzee's novel Disgrace (1999), is investigated within the post-Apartheid policy in South Africa and within the context of patriarchy. Current research analyzes resistance and strategies of the female characters that stand up to being subjects within a culturally patriarchal and colonial society. The novel reveals the former dominant groups in their struggle against the deep transformations in South Africa with its recent withdrawal from racial segregation policy. The inversion of attitudes in a post-Apartheid context is the main difficulty for the white man since the new policy is turned towards a recovery of the Negroes - identity and their recently found authority in the country. The issues involving the white woman Lucy are also investigated. In fact, she is passive after being gang-raped by Negroes. The subjecting characteristic of such an attitude occurs when Lucy becomes the space in which the Negro and the Eurocentric person may meet. Consequently, the black child she bears represents the start of a new policy. However, it may be concluded that, in spite of subjectification traits, the changes in South Africa ha ve not caused sufficient progress and failed to promote equality in the country. Although Apartheid laws are no longer mandatory in South Africa, the ideology of racial segregation still pervades the reconstruction process which turns up to be slower and painful to the Negro. Further, the disparity between the social classes impairs the country's progress and development. These facts show that other strategies and attempts may be needed to reestablish a new order in South Africa. The strategy of the silenced woman in Disgrace is paradoxically the paradigm of reconciliation. Silence and nonemancipatory stance of the female subject are contradictorily the proposed paths for peace by which the white person may collaborate in the social restructure of the country under the aegis of subalternity.